Association of topical glaucoma medications with lacrimal drainage obstruction and eyelid malposition - Quinn, Matthew P; Kratky, Vladimir; Whitehead, Marlo; Gill, Sudeep S; McIsaac, Michael A; Campbell, Robert J (Eye, 2023)
BACKGROUND/OBJECTIVES: Adverse effects of topical glaucoma medications (TGMs) may include development of ocular adnexal disorders. We undertook a study to determine the effect of TGMs on the risk of developing lacrimal drainage obstruction (LDO) and eyelid malposition. SUBJECTS/METHODS: All patients 66 years of age and older in Ontario, Canada initiating TGM and all patients diagnosed with glaucoma/suspected glaucoma but not receiving TGM from 2002 to 2018 were eligible for inclusion in this retrospective cohort study. Using validated healthcare administrative databases, cohorts were identified with TGM and no TGM patients matched 1:2 on sex and birth year. The effect of TGM treatment on risk of surgery for LDO and lid malpositions was estimated using Kaplan-Meier and Cox proportional hazards models. RESULTS: Cohorts included 122,582 patients in the TGM cohort and 232,336 patients in the no TGM cohort. Among the TGM cohort there was decreased event-free survival for entropion (log-rank P < 0.001), trichiasis (P < 0.001), and LDO (P = 0.006), and increased ectropion-free survival (P = 0.007). No difference in ptosis-free survival was detected (P = 0.78). For the TGM cohort there were increased hazards for entropion (hazard ratio [HR] 1.24, 95% confidence interval [CI] 1.12-1.37; P < 0.001), trichiasis (HR 1.74, 95% CI 1.57-1.94; P < 0.001), and LDO (at 15 years: HR 2.39, 95% CI 1.49-3.85; P = 0.004), and a decreased hazard for ectropion (HR 0.89, 95% CI 0.81-0.97; P = 0.008). No association between TGM treatment and ptosis hazard was detected (HR 0.99, 95% CI 0.89-1.09; P = 0.78). CONCLUSIONS: TGMs are associated with an increased risk of undergoing surgery for LDO, entropion, and trichiasis.
Keywords: entropion; Ectropion; Blepharoptosis; glaukom; retrospektivní studie; trichiáza; oční víčka; Entropion; Humans; Trichiasis; Glaucoma; Eyelids; lidé; Retrospective Studies; blefaroptóza; ektropion